A-22 Gender Effects and Self-Reported Symptomatology at Baseline. (18th June 2020) - Horne, K; Gilmore, M; Bennett, R; Lashley, L
ABSTRACT: Objective: To examine potential effects of gender on self-reported symptomatology in athletes who did not report a prior concussion history at baseline using ImPACT. Method: Participants were selected from an archival de-identified sports medicine ImPACT database. The sample (N = 28, 616) consisted of primarily male (58.2%) student athletes in South Florida with a mean age of 15.36 years (SD = 1.332). An exploratory factor analysis performed by Kontos and colleagues (2012) was utilized to categorize ImPACT self-reported symptomatology into four symptom groups: Affective, Sleep, Cognitive, and Vestibular Somatic. An independent samples t-test was conducted to determine the relationship between gender and self-reported symptoms at baseline. Statistical significance was set at p < 0.01. Results: The independent samples t-test determined significant differences (p < .001) between gender and self-reported symptomatology regarding cognitive (d = 0.14), affective (d = 0.30), sleep (d = 0.13), and vestibular somatic symptoms (d = 0.17). Descriptive statistics revealed females on average reported more symptoms than males at baseline. Conclusions: Findings indicate females are more likely to endorse sleep, emotion, and somatic symptoms in comparison to males at baseline. The results suggest that gender may be a mediating factor in regards to self-reported symptomatology, and should be accounted for when comparing baseline assessments to post-injury. Additionally, these results suggest self-reported symptomatology may be an accurate representation of athlete's baseline functioning and are not solely related to post injury complications. Going forward, one's self-reported symptomatology at baseline should be highly considered when clearing athletes for both return to learn and play.